Talc nanoparticles influence on thermoplastic corn starch film properties - Lopez, Olivia Valeria (2015)
Nanocomposite films of TPS with talc particles were obtained by thermo-compression in order to study the effect of this filler on structure, optical, and thermal properties. TPS-talc films showed good appearance and homogeneous thickness. Talc addition increased the amount of rigid phase of nanocomposite films, thus their cross-sections resulted more irregular than those of TPS ones. Talc preferential orientation within matrix and good compatibility between particles and TPS were evidenced. TEM observation showed scattered randomly dispersed individual talc platelets. Matrix crystallinity degree was not significantly affected by particles presence. Nanocomposite films were optically transparent due to the laminar morphology and nanosized particles. Materials microstructure presented glycerol- and starch-rich domains. Talc incorporation higher than 3 % w/w increased softening resistance of nanocomposites as stated by DMA assays. TPS relaxation temperature of glycerol-rich phase was shifted to higher values since talc nanoparticles reduce starch chains mobility.